The World Bank group in Asia : a summary of activities - World Bank ([Washington?], 1963)
"Describes the part played by the World Bank and its affiliates: [International Development Association and International Finance Corporation] in the development of Asia."
Keywords: Loans, Foreign; World Bank; Asia